1996
DOI: 10.1093/ajcn/64.6.903
|View full text |Cite
|
Sign up to set email alerts
|

Early response to the effect of iron fortification in the Venezuelan population

Abstract: In Venezuela a severe economic crisis beginning in 1983 provoked a progressive reduction of the quality and quantity of food consumed by the low socioeconomic strata of the population. In these strata, which represent > or = 80% of the Venezuelan population, we had seen a continuous increase in the prevalence of iron deficiency during that recent decade. As a result, in 1993 the Venezuela Government created the Special Commission for Enrichment of Foods. That same year a fortification program began in which pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
1
6

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(77 citation statements)
references
References 14 publications
3
66
1
6
Order By: Relevance
“…In India, after double fortification of salt with iodine and iron, it was not possible to show a clear impact in reducing anaemia (Sivakumar et al, 2001). On the other hand, successful iron fortification interventions have been conducted in Morocco (Zimmermann et al, 2004), Vietnam (Thuy et al, 2003;Van Thuy et al, 2005), Chile (Hertrampf et al, 1990;Walter et al, 1993), Ghana (Lartey et al, 1999), Venezuela (Layrisse et al, 1996), Guatemala (Viteri et al, 1995) and India (Ballot et al, 1989). However, with a few exceptions the majority of these successful interventions have actually also included encapsulation (Zimmermann et al, 2004) or dietary bioavailability improvements, in the form of ethylenediamine tetraacetic acid (EDTA) (Ballot et al, 1989;Viteri et al, 1995;Thuy et al, 2003;Van Thuy et al, 2005), fish powder (Lartey et al, 1999) or/and ascorbic acid (Hertrampf et al, 1990;Walter et al, 1993) as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In India, after double fortification of salt with iodine and iron, it was not possible to show a clear impact in reducing anaemia (Sivakumar et al, 2001). On the other hand, successful iron fortification interventions have been conducted in Morocco (Zimmermann et al, 2004), Vietnam (Thuy et al, 2003;Van Thuy et al, 2005), Chile (Hertrampf et al, 1990;Walter et al, 1993), Ghana (Lartey et al, 1999), Venezuela (Layrisse et al, 1996), Guatemala (Viteri et al, 1995) and India (Ballot et al, 1989). However, with a few exceptions the majority of these successful interventions have actually also included encapsulation (Zimmermann et al, 2004) or dietary bioavailability improvements, in the form of ethylenediamine tetraacetic acid (EDTA) (Ballot et al, 1989;Viteri et al, 1995;Thuy et al, 2003;Van Thuy et al, 2005), fish powder (Lartey et al, 1999) or/and ascorbic acid (Hertrampf et al, 1990;Walter et al, 1993) as well.…”
Section: Discussionmentioning
confidence: 99%
“…But since no large-scale iron-fortification interventions have been evaluated for effectiveness, few data are available to show the efficacy of iron-fortification interventions in improving iron status (INACG, 2004). Studies of the effects of smaller iron-fortification interventions on iron status in developing countries where fortification has been the only measure taken have been controversial and not completely successful (Layrisse et al, 1996;Sivakumar et al, 2001). Together with observations showing that low iron bioavailability diets can be a cause of iron deficiency anaemia (Zimmermann et al, 2005), this suggests that the bioavailability aspect must also be considered.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in agreement with results reported by ref [44,9], where bioavailability of ferrous fumarate used for food fortification was found to be affected negatively by food inhibitors. In addition, NaFeEDTA was reported to enhance iron absorption and bioavailability from a meal of low iron bioavailability [45,46,47]. This characterstic of NaFeEDTA may have also contributed to the increase in HME from NaFeEDTA containing chick feed.…”
Section: Bioavailability Assaymentioning
confidence: 99%
“…1 Several studies have demonstrated that in children, especially those under the age of five, iron deficiency anemia (IDA) is related, among other alterations, to low scores in mental development and motor activity tests, a fact that may lead to irreversible sequelae even in the presence of adequate treatment. 2,3 Despite the lack of comprehensive national studies, regional data have shown a substantial increase in the prevalence of anemia in Brazil, with this increase being observed among both males and females, from all age groups and all socioeconomic levels of the population.…”
Section: Introductionmentioning
confidence: 99%